Hegemoni dalam Emansipatory: Studi Kasus Advokasi Legalisasi LGBT di Indonesia - Hartanto Wijoyo (Universitas Diponegoro, 2016)
The emergence of polemics in terms of advocating the legalization of LGBT in Indonesia is a domestic phenomenon related to the international politics. LGBT already exist in Indonesia for a long time, and the number is growing, and needs concern. Legalization by 22 countries around the world encourage the LGBT community in Indonesia demands the government acknowledged of the existence in line with the globalization of communication which facilitates freely information flow crossing boundaries of the country. The support the United Nations, United States with a diplomatic device, and funding by UNDP lead LGBT issues become more complex. The phenomenon can be defined as an act of western cultural hegemony attempts to veil emasnsipatory spirit that does not comply with the norms and values of Indonesia. Indonesia needs to counter the hegemony with organic intellectuals to achieve a catharsis conditions, so that Indonesia is able to preserve its norms and values.Keywords: LGBT, hegemony, organic intellectuals, catharsis